DRUGS USED FOR HEARTBURN, AND THEIR CHEMICAL COMPOSITION (Scientific journal of the Fergana State University, 2023)
The article describes the causes of heartburn, some modern drugs used in the treatment of this disease, and their effect on the body, as well as medicinal plants used in traditional medicine, their chemical composition and properties.